Our black sons matter : mothers talk about fears, sorrows, and hopes - Yancy, George; Davidson, Maria del Guadalupe; Hadley, Susan, (Susan Joan), 1967- (Lanham, MD : Rowman & Littlefield, 2016)
"Our Black Sons Matter is a powerful collection of original essays, letters, and poems that addresses both the deep joys and the very real challenges of raising black boys today. From Trayvon Martin to Tamir Rice, the list of young black men who have suffered racial violence continues to grow. Young black people also deal with profound stereotypes and structural barriers. And yet, young black men are often paradoxically revered as icons of cultural cool. Our Black Sons Matter features contributions from women across the racial spectrum who are raising or have raised black sons--whether biologically their sons or not. The book courageously addresses painful trauma, challenges assumptions, and offers insights and hope through the deep bonds between mothers and their children. Both a collective testimony and a collective love letter, Our Black Sons Matter sends the message that black lives matter and speaks with the universal love of all mothers who fear for the lives of their children."--Provided by publisher.
Includes bibliographical references and index.
Keywords: African American young men; African American boys; Mothers and sons -- United States; African Americans -- Family relationships